Pengaruh Bauran Promosi Terhadap Volume Penjualan - Khamdan Suriyok (Ecobuss, 2020)
The purpose of this study was to determine the effect of the promotion mix on sale and to determine the variables which have a dominant effect on sale. The data analysis technique used in this research is descriptive analysis, correlation analysis, and regression analysis. The test result show that the promotion mix variable, namely advertising (X1), has a partially significant effect on sale (Y) as well as a variable that has a dominant effect on sales. And the result of partial regression testing show that the promotion mix variable, namely sale promotion (X2), has a partially insignificant effect on sale.